Methods for evaluation of small scale quality improvement projects. Issue 3 (1st June 2003) - Harvey, G; Wensing, M
Abstract : Evaluation is an integral component of quality improvement and there is much to be learned from the evaluation of small scale quality improvement initiatives at a local level. This type of evaluation is useful for a number of different reasons including monitoring the impact of local projects, identifying and dealing with issues as they arise within a project, comparing local projects to draw lessons, and collecting more detailed information as part of a bigger evaluation project. Focused audits and developmental studies can be used for evaluation within projects, while methods such as multiple case studies and process evaluations can be used to draw generalised lessons from local experiences and to provide examples of successful projects. Evaluations of small scale quality improvement projects help those involved in improvement initiatives to optimise their choice of interventions and use of resources. Important information to add to the knowledge base of quality improvement in health care can be derived by undertaking formal evaluation of local projects, particularly in relation to building theory around the processes of implementation and increasing understanding of the complex change processes involved.